Gigs of their own: reinventing worker cooperativism in the platform economy and its implications for collective action - Bunders, Damion Jonathan (Edward Elgar Publishing, 2021)
Based on the significant collective action problems that gig workers face, sociologists would generally expect that these workers take a mostly individualistic approach to improving their position. Nonetheless, various forms of collective action by gig workers can be observed in practice. This chapter compares worker-owned gig platforms with traditional worker cooperatives in order to derive insights on the chances for collective action in the platform economy. As an 'extreme case' of collective action, worker-owned gig platforms show that the platform economy context potentially helps to overcome some age-old problems of collective action. At the same time, the platform economy brings forth new challenges for workers' collective action. It is concluded that there might be two approaches to solving the social dilemmas involved.